Building Competitive Advantage from the Perspective of Store Atmosphere, Service Quality, and E-WOM - Jati Nugroho; Iwan Hermawan; Inayah, Inayah; Suharmanto, Suharmanto; Luqman Khakim (Cita konsultindo, 2023)
The fashion business in the city of Semarang has very intense competition, so the uniqueness and excellence of the products offered to consumers becomes a challenge. This requires creativity, innovation, and the courage to try new products. The purpose of this study is to measure the effect of Store Atmosphere, Service Quality, and E-WOM (Electronic Word of Mouth) on Competitive Advantage. The problem of this research is